2004
DOI: 10.1515/cclm.2004.016
|View full text |Cite
|
Sign up to set email alerts
|

In vivo total antioxidant capacity: comparison of two different analytical methods

Abstract: Several methods to assess the total antioxidant capacity (TAC) are available. However, the final value of measured TAC in the sample depends on the procedure used in every specific assay. This makes crucial the comparison of different analytical methods. The aim of our study was to evaluate analytical characteristics and laboratory reliability of two different assays: the ferric-reducing ability (FRAP) assay and a new spectrophotometric test (OXY-adsorbent test, Diacron, Italy). Unselected outpatients referred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 19 publications
6
40
2
2
Order By: Relevance
“…In particular, we and others have demonstrated that isoprostanes, markers of lipid peroxidation and reduced antioxidant capacity, are related to an increased risk for cardiovascular disease and correlated with the number of cardiovascular risk factors 5,6) . Other evidence indicates that thiobarbituric acid reactive substance (TBARS, indicators of lipid peroxidation) levels are correlated with endothelial dysfunction and coronary artery disease 11,12) .…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…In particular, we and others have demonstrated that isoprostanes, markers of lipid peroxidation and reduced antioxidant capacity, are related to an increased risk for cardiovascular disease and correlated with the number of cardiovascular risk factors 5,6) . Other evidence indicates that thiobarbituric acid reactive substance (TBARS, indicators of lipid peroxidation) levels are correlated with endothelial dysfunction and coronary artery disease 11,12) .…”
Section: Discussionmentioning
confidence: 81%
“…Other evidence indicates that thiobarbituric acid reactive substance (TBARS, indicators of lipid peroxidation) levels are correlated with endothelial dysfunction and coronary artery disease 11,12) . Specifically, our previous data indicated associations between d-ROMs, OXY-adsorbent and Oxidative-INDEX and the presence and severity of CAD, and the relationship between these biomarkers of oxidative stress and the extent and number of risk factors, including the presence of diabetes, dyslipidemia, hypertension, and smoking habit, and with inflammatory biomarkers 5,6,[8][9][10][11] . Interestingly, a significant inverse correlation between d-ROMs and OXY-adsorbent tests (r =−0.3, p ≤ 0.01) was also observed in our CAD patient cohort.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The shift in the antioxidant/prooxidant equilibrium in favour of oxidative stress represents a crucial determinant in aging and other chronic and degenerative diseases [8][9][10]. Therefore, additional information may be revealed by the evaluation of the overall antioxidant capacity together with index of free radical generation [11][12].…”
Section: Introductionmentioning
confidence: 99%